PENGARUH PEMBERIAN INHALASI KOMBINASI SALMETEROL/FLUTIKASON PROPIONAT TERHADAP KUALITAS HIDUP PENDERITA PENYAKIT PARU OBSTRUKTIF KNONIK STABIL - Refi Sulistiasari (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
It is known that inflammation is the underlying cause of COPD, and this affects to quality of life of the patient. Provision of inhaled therapy combination of LABA and corticosteroids is one of therapy in pharmacology of stable PPOK patients. The aim of this study was to know the benefits of inhalation of 50 g / fluticasone propionate 500 g inhibition in stable COPD patients. The research design is clinical trial. The study was conducted for 3 months and was performed on 26 stable COPD patients divided into two groups: 15 patients for the treatment group and 15 patients for the control group. After the measurements were obtained, there was a significant difference in the quality of life as measured by St. George's Respiratory Questionnaire (SGRQ) (p = 0.001) and COPD Assessment Test (CAT) (0.001) measurements were made twice on the first and thirtieth days.